Wykorzystanie wybranych metod wielowymiarowej analizy porównawczej do oceny poziomu zjawiska przestępczości w powiatach Polski w 2012 roku - Dubiec, Gabriela (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article attempts to identify particularly vulnerable counties which are prone to the phenomenon of crime and to create crime maps using multi-dimensional comparative analysis (MCA). As a tool for comparing Polish counties in terms of crime and identifying factors determining it, the article uses two MCA methods, i.e. the pattern and anti-pattern method, and the Ward method as an example of a hierarchical grouping method. Therefore, a synthetic measure of crime was determined, which replaces the set of many features of the examined objects (in this case they are variables characterising crime) into one aggregated normalised variable. This approach not only enables the assessment of counties using one quantity, but also allows them to be ordered in terms of the phenomenon under consideration.
Keywords: crime; multidimensional analysis; crime determinants; taxonomy; Ward’s method; synthetic measure of development; pattern and anti-pattern method